Expression of MX-1 and OAS-1 Genes in Peripheral Blood Mononuclear Cells during Early Pregnancy in Jersey Crossbred Heifers - Rahul, Girish; Sarath, Thulasiraman; Vijayarani, Kanagaraj; Arunmozhi, Narayanasamy; Pugazharasi, Chidambaram; Nag, Beladakere S. Pradeep (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The present investigation was conducted to study Myxovirus resistance (MX-1) gene expression and 2,5-Oligo-Adenylate Synthetase 1  (OAS-1) gene, present in peripheral blood mononuclear cells and its correlation with early pregnancy in heifers. A total of 24 Jersey crossbred  heifers were selected and synchronized using TRIU-B®, PGF2α, and GnRH. All the experimental animals were fixed time inseminated, and  blood samples were collected on days 0, 14, 15, 16, 17, 18, 19, 20, and 25 post-insemination. The animals were divided into two groups  retrospectively 30-45 days later by pregnancy verification. Blood samples from six pregnant and six non-pregnant heifers were processed  for expression studies of MX-1 and OAS-1 genes by real-time 2-ΔΔCT calculated PCR and their relative expression. The results showed  that MX-1 mRNA levels were not different (p
Keywords: Early pregnancy; Heifers; Gene expression; MX-1 gene; OAS-1 gene; RT-PCR